Clinical spectrum and therapeutic challenges of foreign body aspiration in children: An observational study - Gowthami Adusumilli; Ramesh R Pol; Bhuvaneswari C Yelamali; Raghavendra N Vanaki; Ashok V Badakali (Wolters Kluwer Medknow Publications, 2017)
Objective: The aim of our study is to know the commonest and variable presentation of airway foreign bodies, to study the various parameters like site and nature of foreign body, to know the outcome and complications associated with bronchoscopy. Methods: A hospital based observational study conducted at a teritiary care hospital, Bagalkot between 1st January 2015 to 31st December 2015. Data collected using a preformed questionnaire; proportions and percentages were used to analyze the data. Results: A total of 25 patients were studied, males outnumbered females by a ratio of 6.3:1, youngest child being 9 months. Only 12 out of 25 cases presented with history of foreign body aspiration accounting to 48%. Most common symptoms are cough and hurried breathing; most common signs are retractions and decreased air entry. Most common X-ray finding is unilateral obstructive emphysema. Left main bronchus was the commonest site for foreign body impaction and commonest type was vegetative foreign body. Foreign body was successfully removed in 24 cases. Bronchial spasm was the most common immediate post bronchoscopy complication and bronchopneumonia was most common late complication. One baby expired due to aspiration of vegetative foreign body with complete airway obstruction. Conclusion: Tracheobronchial foreign bodies are difficult to diagnose in children. High index of suspicion for foreign body aspiration should be considered especially when child present with sudden onset respiratory distress and/ or unilateral chest findings, not improving with intravenous antibiotics and 100% oxygenation. Early diagnosis and treatment helps to reduce complications and mortality.